The actress was not on the balcony: testing the Pseudorelative-First Hypothesis in Spanish - De Pedis, Marta; Zawiszewski, Adam; Laka, Itziar (Frontiers in Psychology, 2025)
Strategies for attachment resolution in double-antecedent relative clauses have been widely studied since the late 1980s, when a seminal study by Cuetos and Michell revealed that the principles of Late Closure and Minimal Attachment were met in some languages but not in others. These principles predicted a universal preference for low attachment whereas several studies obtained a high attachment preference in Spanish. Since then, high attachment preference has been reported in a variety of languages and with different methods. There have been several attempts at explaining high attachment preference, but none have succeeded. In 2014, the Pseudorelative-First (PR-First) Hypothesis was proposed: it claims that pseudorelative clauses (PRs) are the reason why some languages reveal a preference for high attachment. In this paper, we test the PR-First Hypothesis by means of two self-paced reading experiments in Spanish. Results (reading times and accuracy scores) show an overall preference for HA regardless of PR availability, indicating that the PR-First Hypothesis cannot account for the variation in attachment preferences found in the literature.